Overview of healthcare in the UK - Grosios, Konstantina (Springer Netherlands, 2010)
The National Health System in the UK has evolved to become one of the largest healthcare systems in the world. At the time of writing of this review (August 2010) the UK government in its 2010 White Paper “Equity and excellence: Liberating the NHS” has announced a strategy on how it will “create a more responsive, patient-centred NHS which achieves outcomes that are among the best in the world”. This review article presents an overview of the UK healthcare system as it currently stands, with emphasis on Predictive, Preventive and Personalised Medicine elements. It aims to serve as the basis for future EPMA articles to expand on and present the changes that will be implemented within the NHS in the forthcoming months.